Peternakan Domba dengan Sistem Kemitraan Inti Plasma - Widianto, Dita Novian; Amam, Amam; Jadmiko, Mochammad Wildan; Harsita, Pradiptya Ayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Plasma core partnerships are one solution for farmers who have limited capital in running a sheep farming business. The success of the sheep farming business process can be achieved if the business is able to obtain profitable results, so that the business can be sustainable. This research aims to analyze the factors that determine the income of sheep farmers using a plasma core partnership system. The research was conducted in January-June 2023 in Jember Regency. This research uses quantitative methods. The research data consists of primary data obtained by observation and secondary data obtained from the Recap of Breeders' Rearing Results (RHPP) of the core company, namely UD Al Fatih Multi Farm. The variables observed were the number of sheep population kept by the partner (X1), the difference in sheep weight (X2), the Daily Body Weight Gain (PBBH) of the sheep (X3), the total weight of sheep feed received by the partner (X4), and the cost of feed consumption (X5 ), and farmer income (Y). The total research sample was 43 breeders (total sampling). Research data was analyzed using quantitative descriptive analysis and multiple linear regression. The results of the research show that the number of sheep populations raised by partners, sheep feed consumption, and the cost of consuming sheep feed have a significant influence on farmer income, but the difference in sheep weight and PBBH has an insignificant influence on farmer income. The conclusion of the research shows that farmers who partner with UD Al Fatih Multi Farm have an average sheep rearing population of 30.41 ± 7.1 head, the average difference in sheep weight after the rearing process is 154.96 ± 66 kg, the average The PBBH of sheep is 0.08 ± 0.03 kg, the average feed consumption is 264.21 ± 4.9 kg, the average feed consumption cost is IDR 3,525,738 ± 1,695,585, and the average income of plama farmers is IDR 4,224,162±1,186,761. The recommendation obtained from this research is that sheep farming with a plasma core partnership system has great potential to be developed.